Synthesis and characterization of thiolated hexanoyl glycol chitosan as a mucoadhesive thermogelling polymer - Cho, Ik Sung (Biomater Res, 2018)
BACKGROUND: Mucoadhesive polymers, which may increase the contact time between the polymer and the tissue, have been widely investigated for pharmaceutical formulations. In this study, we developed a new polysaccharide-based mucoadhesive polymer with thermogelling properties. METHODS: Hexanoyl glycol chitosan (HGC), a new thermogelling polymer, was synthesized by the chemical modification of glycol chitosan using hexanoic anhydride. The HGC was further modified to include thiol groups to improve the mucoadhesive property of thermogelling HGC. The degree of thiolation of the thiolated HGCs (SH-HGCs) was controlled in the range of 5–10% by adjusting the feed molar ratio. The structure of the chemically modified polymers was characterized by (1)H NMR and ATR-FTIR. The sol-gel transition, mucoadhesiveness, and biocompatibility of the polymers were determined by a tube inverting method, rheological measurements, and in vitro cytotoxicity tests, respectively. RESULTS: The aqueous solution (4 wt%) of HGC with approximately 33% substitution showed a sol-gel transition temperature of approximately 41 °C. SH-HGCs demonstrated lower sol-gel transition temperatures (34 ± 1 and 31 ± 1 °С) compared to that of HGC due to the introduction of thiol groups. Rheological studies of aqueous mixture solutions of SH-HGCs and mucin showed that SH-HGCs had stronger mucoadhesiveness than HGC due to the interaction between the thiol groups of SH-HGCs and mucin. Additionally, we confirmed that the thermogelling properties might improve the mucoadhesive force of polymers. Several in vitro cytotoxicity tests showed that SH-HGCs showed little toxicity at concentrations of 0.1–1.0 wt%, indicating good biocompatibility of the polymers. CONCLUSIONS: The resultant thiolated hexanoyl glycol chitosans may play a crucial role in mucoadhesive applications in biomedical areas.